PEMBUATAN GAME “MOVE THAT PLANE” MENGGUNAKAN MARKER DENGAN WEBCAM - Adrian Lewis Haris; Jeanny Pragantha; Rendi Kristyadi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
“Move That Plane” game is created using Unity 3D. “Move that plane” featured a war with aliens in the distant future. Players are conditioned as a pilot and part of the army that has been tasked to save the world. There are components that become elements of games such as enemy, item, and environment. Testing is done with questionnaires filled out by 20 respondents. The obtained results in the form is an increase of design and add more variety for enemy and player plane.